(3CRgGQ GdCacGQ aj LhGgQ GdMLGQs - (3CMeO Hf jhSa GdJjaGTj, TgGH GdOjf CHh GdYHGS,J (B651 (3g` s
(3ChdgG (B:s
(3bGd GdYHO GdabjQ Edi Gddg YR hLd CMeO Hf jhSa GdJjaGTi YaG Gddg Yfg gPG cJGH ZQjH GdhVY YLjH GdLeY YXje GdfaY VefJg PcQ GdGMLGQ GdedhcjI GdJi JhLO ai NRGFf Gdedhc hONGFQ GdQDhSGA s
(3BNQgG (B:s
(3Ke GSad GdMjWGf HeSbdI RLGL UbdkG LjOkG aEfg jUjQ cCfg dhf GdOQ hbjeJg hKefg GdGhbjg ef LjOg HOQge fbQI Je GdcJGH HMeO Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HQSe NRGfI GdLfGH GdYGdi Gdehdhi GdGejQi GdcHjQi GdSjai GdNGVci Gdedci GdCTQai s
(3cJHJ HYV GdCdaGX HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdcjejGA h GdWHjYjGJs